Giardiasis and Subsequent Irritable Bowel Syndrome: A Longitudinal Cohort Study Using Health Insurance Data. (23rd February 2017) - Nakao, Jolene H.; Collier, Sarah A.; Gargano, Julia W.
Abstract: Background: Giardia intestinalis is the most commonly reported human intestinal parasite in the United States. Increased incidence of chronic gastrointestinal complaints has been reported after some giardiasis outbreaks. We examined the relationship between giardiasis diagnosis and irritable bowel syndrome (IBS) diagnosis. Methods: We used the 2006–2010 MarketScan commercial insurance database. Persons with at least 1 giardiasis diagnosis were individually matched on age group, sex, and enrollment length in months to 5 persons without a giardiasis diagnosis. Persons diagnosed with IBS before the date of study entry were excluded. We calculated crude incidence rates (IRs) and developed Cox proportional hazards models. Results: The matched cohort included 3935 persons with giardiasis and 19663 persons without giardiasis. One-year incidence of IBS was higher in persons with giardiasis (IR = 37.7/1000 person-years vs 4.4/1000 person-years). The unadjusted hazard ratio was 4.8 (95% confidence interval [CI] = 3.6–6.4), attenuated slightly to 3.9 (95% CI = 2.9–5.4) after adjusting for anxiety, depression, and healthcare utilization. Conclusions: In a large insurance database, individuals diagnosed with giardiasis were more likely to have a subsequent IBS diagnosis, despite accounting for confounders. Future research on risk factors for IBS among giardiasis patients and the pathophysiology of postinfectious IBS is needed.